The Contribution of Socio-economic Position to the Excesses of Violence and Intimate Partner Violence Among Aboriginal Versus Non-Aboriginal Women in Canada - Daoud, Nihaya (Can J Public Health, 2013)
OBJECTIVE: To examine the contribution of socio-economic position (SEP) in explaining the excess of any abuse and intimate partner violence (IPV) among Aboriginal versus non-Aboriginal women in Canada. This comparison has not been studied before. METHODS: We conducted logistic regression analysis, using nationwide data from a weighted sample of 57,318 Canadian-born mothers of singletons who participated in the Canadian Maternity Experiences Survey 2006-7. RESULTS: The unadjusted odds of any abuse and IPV were almost four times higher among Aboriginal compared to non-Aboriginal mothers; OR 3.91 (95% CI 3.12-4.89) and OR 3.78 (2.87-4.97), respectively. Adjustment for SEP reduced the unadjusted OR of any abuse and IPV by almost 40%. However, even with this adjustment, the odds of any abuse and IPV for Aboriginal mothers remained twice that of non-Aboriginal mothers; OR 2.34 (1.82-2.99) and OR 2.19 (1.60-3.00), respectively. CONCLUSIONS: SEP is a predominant contributor to the excess of abuse against Aboriginal vs. non-Aboriginal women in Canada. Reducing violence against Aboriginal women can be achieved mostly by improving their SEP, and simultaneously be informed by social processes and services that can mitigate abuse. The fact that SEP did not fully explain the excess of abuse among the Aboriginal women might lend support to “colonization or postcolonial theories,” and related contextual factors such as differences in community social resources (e.g., social capital) and services. The effect of these factors on the excess of abuse warrants future research.